O LÚDICO VIA FÁBULAS EM ATENDIMENTO PSICOTERAPÊUTICO: UM ESTUDO DE CASO CLÍNICO DE MOBBING - Santos, Vilma Moreira dos (2008)
The research carried out validates the use of fables within the psychotherapy treatment process of a patient exhibiting conditions of mobbing, depression and panic syndrome. The study was carried out using evaluative case studies. The research is developed by way of evaluative case study which consisted of 116 weekly sessions. Initially, a clinical diagnosis was carried out and elaborated from a picture drawn of a person, (extracted from the projective test: House, Tree and Person). The sessions included various means of information discover techniques including interview, unaided discussion and observation. The sessions are carried out with randomly fables, using relaxation technique from Schultz and Jacobson, with dream interpretation and instruct patients to view movies. The achievement is verify what the fables contribute to the patient on the positive way of understanding more easily on the psychotherapists discoveries, if laying down his resistances of speaking about his thoughts and amplify the symbolic consciousness. The first intervention moment lasts for 16 months, the second lasts for 4 months in which the second picture is drawn and the third moment lasts 9 months when the final picture is requested. At the first moment, favorable conditions with emotional support are provided to the patient in an attempt to release illusion, as per Winnicot s vision. A mobbing situation is then employed, in which the patient also experiences depression, panic syndrome, a high level of personal and professional self demand and renders the patient passive within relationships. At the end of this moment, the patient begins to projects their aggression externally rather than internalising it in a more positive and socially accepted way. The second moment is predominated by the acceptance of herself, being able to see how much she was hurting, showing more confidence, communicating and facing her inability to better affectionate difficulties. In the third moment, the patient shows being secure and happy, a high level of self grooming and starts to feel good about being noticed in society. The patient Illustrates having learnt to stand up for herself and confronts situations with more confidence. Further she is outwarding projecting the positive changes in her life, smiling frequently. The evolutive analysis of the picture drawn confirms the radical development of the patient. The use of fables was well accepted by the patient, who managed to get closer and face her problems and learn how to deal with them in a healthier manner. The results also indicate that the relaxation techniques associated with the fables contributed to a wider and deeper assimilation from the patient. The process illustrated the case study is gradually developed in 24 parts, properly analyzed in regards to the moments described.(AU)